The Ekpyrotic Scenario - Năstase, Horaţiu [UNESP] (My University, 2019)
In this chapter we will describe the ekpyrotic scenario, which is an alternative to inflation, inspired from string theory, defined in a 2001 paper by Khoury, Ovrut, Steinhardt and Turok. The general idea is that we have two “end of the world” branes that move towards each other in a fifth direction, and their collision represents the Big Bang.